PREVENTION AND TREATMENT OF DIAPER DERMATITIS IN NEONATAL CARE HOSPITAL - I. I. Ryumina ("Paediatrician" Publishers LLC, 2015)
The article is devoted to the relevant problem of pediatrics - treatment of acute respiratory infections in children. It examines the feasibility of a comprehensive treatment of colds in children with mandatory use of non-sedating antihistamines that increase the effectiveness of conventional treatment and prevent the development of allergic complications.